PI3K p110δ Is Expressed by gp38(−)CD31(+) and gp38(+)CD31(+) Spleen Stromal Cells and Regulates Their CCL19, CCL21, and LTβR mRNA Levels - Zotes, Teresa M. (Public Library of Science, 2013)
The role of p110δ PI3K in lymphoid cells has been studied extensively, showing its importance in immune cell differentiation, activation and development. Altered T cell localization in p110δ-deficient mouse spleen suggested a role for p110δ in non-hematopoietic stromal cells, which maintain hematopoietic cell segregation. We tested this hypothesis using p110δ(WT/WT) mouse bone marrow to reconstitute lethally irradiated p110δ(WT/WT) or p110δ(D910A/D910A) (which express catalytically inactive p110δ) recipients, and studied localization, number and percentage of hematopoietic cell subsets in spleen and lymph nodes, in homeostatic conditions and after antigen stimulation. These analyses showed diffuse T cell areas in p110δ(D910A/D910A) and in reconstituted p110δ(D910A/D910A) mice in homeostatic conditions. In these mice, spleen CD4(+) and CD8(+) T cell numbers did not increase in response to antigen, suggesting that a p110δ(D910A/D910A) stroma defect impedes correct T cell response. FACS analysis of spleen stromal cell populations showed a decrease in the percentage of gp38(−)CD31(+) cells in p110δ(D910A/D910A) mice. qRT-PCR studies detected p110δ mRNA expression in p110δ(WT/WT) spleen gp38(−)CD31(+) and gp38(+)CD31(+) subsets, which was reduced in p110δ(D910A/D910A) spleen. Lack of p110δ activity in these cell populations correlated with lower LTβR, CCL19 and CCL21 mRNA levels; these molecules participate in T cell localization to specific spleen areas. Our results could explain the lower T cell numbers and more diffuse T cell areas found in p110δ(D910A/D910A) mouse spleen, as well as the lower T cell expansion after antigen stimulation in p110δ(D910A/D910A) compared with p110δ(WT/WT) mice.